2003
DOI: 10.1177/106342660301100203
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of the Effectiveness of Intensive In-Home Crisis Services for Children and Their Families

Abstract: In this article, we describe the outcomes associated with a 3-year research demonstration project. It is the second of a two-part article concerned with this research conducted in the Bronx, New York, to examine the efficacy of three models of intensive in-home services—Home-Based Crisis Intervention (HBCI), Enhanced Home-Based Crisis Intervention (HBCI+),and Crisis Case Management—as alternatives to hospitalization for children experiencing a psychiatric crisis. In Part I (Evans, Boothroyd, & Armstrong, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
83
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(86 citation statements)
references
References 12 publications
2
83
0
1
Order By: Relevance
“…Of note is the authors' reporting that "5% to 10% of the children enrolled in the in-home services did require hospitalization during the intervention period. These in-home programs did not eliminate the necessity of hospitalization for some children who posed a danger to themselves" [131,132]. The Dawn Project in Marion County, Indiana [133], developed as a system of care model, produced mixed results when examining levels of restrictiveness and degrees of recidivism in its served population.…”
Section: Systems Of Carementioning
confidence: 99%
“…Of note is the authors' reporting that "5% to 10% of the children enrolled in the in-home services did require hospitalization during the intervention period. These in-home programs did not eliminate the necessity of hospitalization for some children who posed a danger to themselves" [131,132]. The Dawn Project in Marion County, Indiana [133], developed as a system of care model, produced mixed results when examining levels of restrictiveness and degrees of recidivism in its served population.…”
Section: Systems Of Carementioning
confidence: 99%
“…One analysis of 600 HMO patients found that those who received home-based crisis intervention had approximately four times fewer behavioral health readmissions than those patients who did not receive in-home services (Pigott & Trott, 1993). Home-based care has been found to have good treatment outcomes for (a) people with serious mental illness (Warner, 1997;Wasylenki, Gehrs, Goering, & Toner, 1997), (b) substance abusers (Gruber, Fleetwood, & Herring, 2001), as well as (c) children, adolescents, and their families (Evans et al, 2003;Henggeler, Schoenwald, Borduin, Rowland, & Cunningham, 2003;Sheidow & Woodford, 2003).…”
mentioning
confidence: 95%
“…Evans et al (2003) noted that little research is available on programs that provide home services to children and families experiencing psychiatric crises. Additionally, Lindblad-Goldberg, Dore, and Stern (1998), in their comprehensive guide to providing home-based therapy to families, reported that outcomes research on in-home services to children is limited.…”
mentioning
confidence: 97%
“…At the service layer, population analysis indicated a high prevalence of disruptive behavior problems and an increasing prevalence of comorbidity (about 75% of youth had multiple diagnoses at intake). At the exosystem layer, the research literature suggested community-based alternatives might be effective (e.g., Henggeler et al, 1999;Evans et al, 2003;Wilmshurst, 2002). At the system layer, local policy prioritized delivery of least restrictive but effective services.…”
Section: A Service System Examplementioning
confidence: 99%